2022
DOI: 10.1051/0004-6361/202141107
|View full text |Cite
|
Sign up to set email alerts
|

The eROSITA view of the Abell 3391/95 field: Case study from the Magneticum cosmological simulation

Abstract: Context. Clusters of galaxies reside at the nodes of the cosmic web, interconnected by filamentary structures that contain tenuous diffuse gas, especially in the warm-hot phase. Galaxy clusters grow by mergers of smaller objects and gas that are mainly accreted through these large-scale filaments. For the first time, the large-scale cosmic structure and a long gas-emission filament have been captured by eROSITA on board the Spectrum-Roentgen-Gamma mission in a direct X-ray observation of the A3391/95 field. Ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 98 publications
0
8
0
Order By: Relevance
“…Furthermore, if an emission bridge does connect the two clusters, the eRASS image will provide its observation. More generally, given the early eROSITA results on cluster outskirts and infall regions (e.g., Reiprich et al 2021;Ghirardini et al 2021;Churazov et al 2021;Veronica et al 2022;Whelan et al 2021;Sanders et al 2022), and given the close correspondence to similar structures observed in cosmological hydrodynamical simulations (e.g., Biffi et al 2022), we may expect that bridges and clumpy filaments will be discovered in several more nearby systems in the future in the eRASS. These systems can then be studied in detail after the eight surveys are completed using the SRG/eROSITA scanning mode, with which areas of tens of square degrees can be scanned efficiently, homogeneously, and deeply.…”
Section: Discussionmentioning
confidence: 72%
“…Furthermore, if an emission bridge does connect the two clusters, the eRASS image will provide its observation. More generally, given the early eROSITA results on cluster outskirts and infall regions (e.g., Reiprich et al 2021;Ghirardini et al 2021;Churazov et al 2021;Veronica et al 2022;Whelan et al 2021;Sanders et al 2022), and given the close correspondence to similar structures observed in cosmological hydrodynamical simulations (e.g., Biffi et al 2022), we may expect that bridges and clumpy filaments will be discovered in several more nearby systems in the future in the eRASS. These systems can then be studied in detail after the eight surveys are completed using the SRG/eROSITA scanning mode, with which areas of tens of square degrees can be scanned efficiently, homogeneously, and deeply.…”
Section: Discussionmentioning
confidence: 72%
“…After analysing the full baryonic content of cosmic filaments, let us now focus our analysis only on the gaseous component, whose observation is the most challenging nowadays. Indeed, despite recent detection of the SZ effect around filaments (see e.g., de Graaff et al 2019 andTanimura et al 2020a results), and studies of X-ray emission of filament gas (see e.g., Tanimura et al 2020b andBiffi et al 2022 respectively in ROSAT and in the very recent eROSITA data), the gaseous content of cosmic filaments is still not fully constrained in observations. In order to help future studies, we provide scaling relations between gas density, temperature, and pressure, derived from the analysis of the TNG300-1 simulation.…”
Section: Scaling Relations With Gas Temperature and Pressurementioning
confidence: 99%
“…The detection of baryons around filaments thus represents a challenge which demands different observational approaches and techniques. For example, by observing individual pairs of clusters, Tittley & Henriksen (2001), Werner et al (2008), Planck Collaboration VIII (2013), Sugawara et al (2017), Akamatsu et al (2017), Alvarez et al (2018), Bonjean et al (2018), Connor et al (2018), Connor et al (2019), Govoni et al (2019), Hincks et al (2022), and Biffi et al (2022) (among others) have detected filaments of scales of a few megaparsecs, acting as bridges of matter between the cluster pairs. Using statistical approaches, some of the properties of these bridges (such as their density, temperature, or magnetic field strength) have been constrained thanks to stacking techniques (e.g., Tanimura et al 2019;de Graaff et al 2019;Vernstrom et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The Magneticum Pathfinder simulations 5 (see Biffi et al 2022) are cosmological hydrodynamical simulations of a large cosmic volume. A light cone is constructed from the so-called Box2 at high resolution ("hr"), which comprises a comoving volume of (352 h −1 cMpc) 3 , resolved with 2 × 1584 3 particles.…”
Section: Magneticum Pathfinder Simulationsmentioning
confidence: 99%